Characterization and pathogenicity of soil borne pathogens inducing root rot symptoms in common bean in Rwanda - Mukamuhirwa, Floride; Butare, Lewis; Ruhakana, Albert; Uzayisenga, Bellancile; Mukantwali, Christine; Musoni, Augustine; Mukankusi, Clare Mugisha (Valley International, 2018)
Though Rwanda is among the highest common bean producers and consumers, this crop is still challenged by different factors including root rot diseases resulting in low yield potential. Root rot diseases can cause up to 100% of yield loss. Despite different soil borne pathogens causing bean root rot diseases; there is no recent literature that clearly documents the most aggressive ones affecting common beans in Rwanda. This study aimed at identifying the root rot pathogens affecting bean crop in Rwanda. A survey was conducted to collect bean samples showing root rot symptoms in 12 agro -ecological zones where bean crop is mostly grown. The selection of samples was based on the level of contamination and the purity of cultures. A total number of 132 samples were therefore selected and considered for further analysis. The pathogen isolation was done in Rubona at Rwanda Agriculture and Animal Resources Development Board (RAB) Biotechnology and Pathology laboratory. Structural characterization of soil borne pathogens was also carried out along with pathogenicity evaluation. The growth rate of identified pathogens were significantly different (P<0.001). Significant differences were observed among isolates inoculated on both plantlets and seeds (P<001). Four root rot diseases were identified and characterized including Rhizoctonia spp, Fusarium spp,Sclerotium spp and several Pythium spp. The four pathogens were mostly observed in Northern and Southern parts of Rwanda than East and Western parts of Rwanda. Morphological characterization showed that Fusarium spp, Rhizoctonia spp and Sclerotium spp were predominant than Pythium species. Fusarium spp was identified as the most predominant fungal pathogen while Sclerotium spp was the most virulent pathogen. The present study suggests bean root rot disease control program to reduce losses associated with these diseases especially the use of resistant varieties since the fungi are widespread and survive in soils for a long period of time.